Analysis of the Practice of Key Actors in the European Union Risk Assessment of the Influence of Chemical Substances On the Environment and Human Health on the Background of Modern Interactive Development - Крайнюков, О. М.; Якушева, А. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2017)
Purpose. An analysis of the peculiarities of the main management actors for the risk assessment due to exposure to chemicals on the environment and human health.. Methods. Theoretical analysis and synthesis. Results. There are presented the analysis of the functioning of the major European Union relating to the regulation of normative principles of risk assessment, due to the impact of chemicals on the environment and public health. Thus were revealed major issues, the solution of which requires the latest developments, which would include a comprehensive approach. One of these modern developments have MERLIN-Expo, the main advantages of this tool are presented in this article. Conclusions. There is a need to develop a new comprehensive software, modular design which would allow to assess the impact of complex dynamic systems that evolve over time. MERLIN-Expo covers the entire chain of exposure assessment, which is the most "weak" place in the overall risk assessment.